The effect and feasibility of the SIMS programme to improve preschool children's oral hygiene level and related behaviours: A cluster randomised control trial / Nurul Hayati Anwar - Nurul Hayati, Anwar (2020)
Background: The preschool oral healthcare programme (POHP) was introduced by the Ministry of Health in 1984 to provide oral healthcare to 5-6-year-old children in Malaysia. Due to some limitations, a new programme called the ‘Senyuman Indah Milik Semua’ Programme (SIMSP) was introduced with the aim to improvise the POHP. In the SIMSP, a triad of dental therapists (DTs), teachers, and parents was set up to promote children’s oral hygiene level, oral health behaviours (OHBs), and parents’ oral health literacy (OHL). The POHP only involved DTs. Objectives: The primary objective of the study was to assess the effect of SIMSP versus POHP on oral hygiene level of 5-6-year-old children in the Kampar District, Perak over 6 months. The secondary objectives were: (i) to assess the impact of SIMSP versus POHP over 6 months in terms of children’s OHBs and parents’ OHL; (ii) to assess the implementation fidelity of SIMSP’s protocol; and (iii) to explore the process implementation of SIMSP from the perspectives of the dental team. Methods: This study was a pragmatic, cluster-randomised, parallel-group, matched pair, examiner-blind, controlled trial with a 1:1 allocation ratio where preschools in Kampar district were the clusters. Using computer generated numbers, 14 government preschools were allocated to intervention (SIMSP) and another 14 to control (POHP) groups with allocation concealed at cluster level (317 sample per group). Children and parents who fulfilled the inclusion criteria were enrolled by DTs. The study tools included a questionnaire to assess demographics and children’s OHBs, the International Caries Detection and Assessment System (ICDAS), the Oral Cleanliness index, and the Malay version of Dental Health Literacy Assessment Instrument (Malay-DHLAI). Data were collected before intervention, and again after 6 months. Implementation fidelity data was self-reported by DTs and teachers. Focus group discussions (FGD) were conducted among DTs and health assistants (HA) in the SIMSP. Quantitative data were analysed iv using SPSS software. Qualitative data were transcribed verbatim and thematically analysed using Nvivo software. Results: At 6-month, 83.4% of children in the SIMSP and 76.4% in POHP completed oral examinations, while response rates for questionnaire was 91.5% and 81.1%, respectively. Mean plaque score decrement was higher in SIMSP than POHP (ES = +0.64). Significantly more SIMSP children took carbonated drinks <1-3x/week (p = 0.033). Parents in the SIMSP had a significantly higher mean knowledge score (mean = 0.54, SD = 2.75, p = 0.024) and higher OHL scores (ES = +0.97) than parents in POHP. The implementation fidelity data showed majority of parents (83.1%) attended the parentDT meetings, majority of teachers delivered the in-class oral health lessons including worksheets (96.8%) and supervised daily toothbrushing (93.7%), and all DTs delivered the oral health infographics to parents (100%). FGD participants perceived that SIMSP was an appropriate programme, effective to improve parents’ OHL, and received good support from the administrators. The main barrier was to get full parental involvement in the SIMSP. Recommendations for improvement included a dental officer in the SIMSP, gain feedback from other stakeholders, and collaborate with private sectors on the SIMSP. Conclusion: The SIMSP was shown to be effective in reducing children’s dental plaque scores, carbonated soft drinks intake, and improving parental OHL than the POHP over 6 months. The SIMSP’s implementation fidelity was high, and the programme was perceived as acceptable by the dental team with rooms for improvement. Keywords: dental plaque, oral hygiene, preschool, child, Malaysia, behaviour, health literacy